2022
DOI: 10.3390/v14051064
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Viral Proteins to the Synergy of Influenza and Bacterial Co-Infection

Abstract: A severe course of acute respiratory disease caused by influenza A virus (IAV) infection is often linked with subsequent bacterial superinfection, which is difficult to cure. Thus, synergistic influenza–bacterial co-infection represents a serious medical problem. The pathogenic changes in the infected host are accelerated as a consequence of IAV infection, reflecting its impact on the host immune response. IAV infection triggers a complex process linked with the blocking of innate and adaptive immune mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 288 publications
(386 reference statements)
0
11
0
Order By: Relevance
“…Influenza A proteins may play a role in the progression of bacterial superinfection, in which neuraminidase promotes entry to receptors and nutrients for S. pneumoniae; other proteins, such as nonstructural protein 1 (NS1) and PB1-F2, disrupt the regulation of the interferon response and inflammatory process. 20 In our study, the most common coinfecting bacterial respiratory pathogens were Staphylococcus aureus, followed by S. pneumoniae and Haemophilus influenzae. A meta-analysis and systemic review pointed out that the predominant coinfecting organism in the studies was S. pneumoniae, followed by S. aureus, but many other organisms were also found to cause infections.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Influenza A proteins may play a role in the progression of bacterial superinfection, in which neuraminidase promotes entry to receptors and nutrients for S. pneumoniae; other proteins, such as nonstructural protein 1 (NS1) and PB1-F2, disrupt the regulation of the interferon response and inflammatory process. 20 In our study, the most common coinfecting bacterial respiratory pathogens were Staphylococcus aureus, followed by S. pneumoniae and Haemophilus influenzae. A meta-analysis and systemic review pointed out that the predominant coinfecting organism in the studies was S. pneumoniae, followed by S. aureus, but many other organisms were also found to cause infections.…”
Section: Discussionmentioning
confidence: 57%
“…Influenza virus paves the way for subsequent bacterial infection by disrupting the anatomic barrier or mucosal surface in the respiratory system. Influenza A proteins may play a role in the progression of bacterial superinfection, in which neuraminidase promotes entry to receptors and nutrients for S. pneumoniae ; other proteins, such as nonstructural protein 1 (NS1) and PB1‐F2, disrupt the regulation of the interferon response and inflammatory process 20 . In our study, the most common coinfecting bacterial respiratory pathogens were Staphylococcus aureus , followed by S. pneumoniae and Haemophilus influenzae .…”
Section: Discussionmentioning
confidence: 70%
“…A virus and Streptococcus pneumonia [4,5] or Human Immunodeficiency Virus (HIV) and Mycobacterium tuberculosis [6][7][8]. Synergy has also been reported between viruses such as Herpes virus simplex and HIV [9,10].…”
Section: Fatal Polymicrobial Synergy Has Been Reported Between Viruse...mentioning
confidence: 99%
“…The severity of the disease is influenced by many factors, including the virulence of the virus strain, which caused the infection, but especially by the status of the host immune system. These factors determine whether the common secondary bacterial infection, in praxis often suppressed by the application of antibiotics, will be associated with the primary viral infection (Mikušová et al, 2022). However, antibiotics may not help to cure the bacterial co-infection if the infected individuals are immuno-compromised or suffer from other chronic diseases (McCullers, 2004(McCullers, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…However, antibiotics may not help to cure the bacterial co-infection if the infected individuals are immuno-compromised or suffer from other chronic diseases (McCullers, 2004(McCullers, , 2011. It was shown that a synergism occurs during influenza and bacteria coinfection (Kash and Taubenberger, 2015;Karlson et al, 2017;Mikušová et al, 2022). Because the influenza infection causes the damage of the respiratory epithelium, the accessibility of epithelial cell surfaces for bacterial infection is increased and, subsequently, u n c o r r e c t e d…”
Section: Introductionmentioning
confidence: 99%